THE INFLUENCE OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE ONE-STOP INVESTMENT AND INTEGRATED SERVICE OFFICE OF THE NORTH LAMPUNG DISTRICT - Jayanti, Eva Yani; Nuzleha, Nuzleha (University of Sang Bumi Ruwa Jurai, 2024)
The research objective in this thesis is to examine the effect of Work Environment and Work Motivation on Employee Performance at the Investment Office and One-Door Integrated Service of North Lampung Regency. The research method used is the Quantitative Analysis Method, this research uses a census research method which according to Suharsimi Arikunto if the research object is less than 100 then it is better to take all, then if the number is more than 100 then it can be taken between 10-30%. According to existing data, the respondents amounted to 39 populations. The results showed that the work environment had a positive effect on the performance of employees of the Investment Office and One-Door Integrated Services of North Lampung Regency with an influence contribution of 57.3% and the remaining 42.7% was explained by other variables not studied in this study. Furthermore, Work Motivation also has a positive effect on Employee Performance with an influence contribution of 65.6%, the remaining 34.4% is explained by other variables not examined in this study. The regression test shows that together there is a positive influence between Work Environment and Work Motivation on Employee Performance. The magnitude of the influence of the two variables X1 and X2 on Y is 73.7%, and the remaining 26.3% is influenced by other factors not examined in this study.